Sphingosine-1-phosphate receptor 3 promotes leukocyte rolling by mobilizing endothelial P-selectin - Nussbaum, Claudia (2015)
Ludwig Maximilians Universität München. Walter Brendel Center, Münche, Germany / Ludwig Maximilians University München. Dr v. Haunersches Children’s Hospital. München, Germany.